Plant genotype-specific archaeal and bacterial endophytes but similar Bacillus antagonists colonize Mediterranean olive trees - Müller, Henry; Berg, Christian; Landa, Blanca B.; Auerbach, Anna; Moissl-Eichinger, Christine; Berg, Gabriele (Frontiers in Microbiology, 2015)
Endophytes have an intimate and often symbiotic interaction with their hosts. Less is known about the composition and function of endophytes in trees. In order to evaluate our hypothesis that plant genotype and origin have a strong impact on both, endophytes of leaves from 10 Olea europaea L. cultivars from the Mediterranean basin growing at a single agricultural site in Spain and from nine wild olive trees located in natural habitats in Greece, Cyprus and on Madeira Island were studied. The composition of the bacterial endophytic communities as revealed by 16S rRNA gene amplicon sequencing and the subsequent PCoA analysis showed a strong correlation to the plant genotypes. The bacterial distribution patterns were congruent with the plant origins in “Eastern” and “Western” areas of the Mediterranean basin. Subsequently, the endophytic microbiome of wild olives was shown to be closely related to those of cultivated olives of the corresponding geographic origins. The olive leaf endosphere harbored mostly Proteobacteria, followed by Firmicutes, Actinobacteria and Bacteroidetes. The detection of a high portion of archaeal taxa belonging to the phyla Thaumarchaeota, Crenarchaeota and Euryarchaeota in the amplicon libraries was an unexpected discovery, which was confirmed by quantitative real-time PCR revealing an archaeal portion of up to 35.8%. Although the function of these Archaea for their host plant remains speculative, this finding suggests a significant relevance of archaeal endophytes for plant-microbe interactions. In addition, the antagonistic potential of culturable endophytes was determined; all isolates with antagonistic activity against the olive-pathogenic fungus Verticillium dahliae Kleb. belong to Bacillus amyloliquefaciens. In contrast to the specific global structural diversity, BOX-fingerprints of the antagonistic Bacillus isolates were highly similar and independent of the olive genotype from which they were isolated.